1997
DOI: 10.1002/(sici)1097-458x(199704)35:4<273::aid-omr73>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide-Crown Ether Mixtures as Chiral NMR Shift Reagents for Amino Acid Esters, Amines and Amino Alcohols

Abstract: Two chiral crown ethers, 2,3:4,5‐bis[1,2‐(3‐phenylnaphtho)‐1,6,9,12,15,18‐hexaoxacycloeicosa‐2,4‐diene and 1,2:5,6‐di‐O‐isopropylidene‐3,4‐[(tert‐butylbenzenediyl)bis(oxyethoxy)ethyl‐D‐mannitol, were evaluated as organic‐soluble chiral NMR resolving agents. The crown ethers are useful resolving agents for protonated amino acid esters, amines and amino alcohols. Enantiodiscrimination with the crown ethers is better in methanol than in acetonitrile or chloroform. Organic‐soluble lanthanide tetrakis(β‐diketonate)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…This behavior indicates on some sort of intermolecular binding, possibly a hydrogen bonding between tetrapeptide 1 and crown ether selector. This assumption is supported by older studies, 28 where shielding effect has been observed for amino acid complexes upon hydrogen bonding with CR (+) selector. However, according to the near identical proton chemical shift differences (ΔΔδ ( llll ‐ dddd ) ~ 0) of formed complexes between llll and dddd enantiomers of tetrapeptide 1 , represented in Table 2, it could be speculated that both enantiomers undergo similar (non‐enantioselective) hydrogen bonding pattern between protonated ε‐NH 2 group in Lys moiety and the oxygens of crown ether selectors.…”
Section: Resultssupporting
confidence: 54%
“…This behavior indicates on some sort of intermolecular binding, possibly a hydrogen bonding between tetrapeptide 1 and crown ether selector. This assumption is supported by older studies, 28 where shielding effect has been observed for amino acid complexes upon hydrogen bonding with CR (+) selector. However, according to the near identical proton chemical shift differences (ΔΔδ ( llll ‐ dddd ) ~ 0) of formed complexes between llll and dddd enantiomers of tetrapeptide 1 , represented in Table 2, it could be speculated that both enantiomers undergo similar (non‐enantioselective) hydrogen bonding pattern between protonated ε‐NH 2 group in Lys moiety and the oxygens of crown ether selectors.…”
Section: Resultssupporting
confidence: 54%
“…Enantiopurity of amino alcohols is important in this context as (S)-propranolol is an active beta-blocker, whereas the (R)-isomer is ineffective in this application but has utility as a potential contraceptive. [24] A universal noncovalent chiral shift reagent for the determination of relative configuration by NMR spectroscopy does not exist and the chiral recognition of amino alcohols has been achieved using several chiral shift reagents, including arylcarboxylic acids, [25][26][27] atropisomers, [28] calixarenes/ resorcinarenes, [29][30][31][32][33][34][35][36] cyclodextrins, [37] crown ethers, [38][39][40] phosphorous-containing reagents, [41][42][43][44] and metallocomplexes, [45,46] amongst others. [47][48][49][50] The separation of amino alcohols has been almost exclusively limited to organic solvents except for resorcinarene and cyclodextrin hosts which have displayed separation in aqueous media.…”
Section: Application Of {Mo 132 (Lactate) 30 } Structures As Chiral Shift Reagentsmentioning
confidence: 99%